Comparison of methane, nitrous oxide fluxes and CO2 respiration rates from a Mediterranean cork oak ecosystem and improved pasture - Shvaleva, Alla; e Silva, Filipe; Costa, Joaquim Miguel; Correia, Alexandra; Anderson, Margaret; Lobo-do-Vale, Raquel; Fangueiro, David; Bicho, Catarina; Pereira, Joo Santos; Chaves, Maria Manuela; Skiba, Ute; Cruz, Cristina (PLANT AND SOIL, 2014)
During the recent decades, cork oak (Q. suber) mortality has been increasing in Mediterranean oak woodland endangering the economical and environmental sustainability of the ``montado{''} ecosystem. This fact in combination with climate change and conversion of forestland to pasture may significantly affect the soil-atmosphere greenhouse gases (GHGs) exchange. Our study evaluates the impact of oak trees as compared to pasture on net ecosystem GHG (CH4, N2O, and CO2) exchange as well as the main environmental factors influencing this exchange. We used field chamber measurements for the collection of GHGs under three different conditions: 1) open area (OA), 2) under tree canopy area (UC) and 3) improved pasture (IP). Experiments were done under typical Mediterranean climate at central Portugal in 2010 and 2011. The UC had higher nitrification potential, soil C/N ratio, electrical conductivity, litter input and soil organic matter (SOM) than OA and IP. SOM positively correlated with soil CH4 and N2O fluxes but not with soil CO2 respiration rates. Soil water content (SWC) drives both CH4 and N2O fluxes. Under certain conditions, when SWC reached a threshold (7 % for CH4 and 3 % for N2O) the result was net uptake and that net uptake increased with SWC. This was the case for the UC and OA. Conversely, for the IP soil water content above 4 % promoted net CH4 release. Our results show that cork oak influences soil properties and consequently GHGs fluxes. In the UC the input of litter for SOM together with soil moisture, favoured microbiological activity and related GHGs fluxes. Soil temperature is a secondary factor in the studied conditions. Our results also emphasized the potential impact posed by decreased cork oak tree density in the functioning of the ``montado{''} ecosystem.
Keywords: evergreen oak; Greenhouse gases; litter; Mediterranean; organic matter; Root density

Impact of the invasive tree black locust on soil properties of Mediterranean stone pine-holm oak forests - De Marco, Anna; Arena, Carmen; Giordano, Maria; De Santo, Amalia Virzo (PLANT AND SOIL, 2013)
Invasion by N-2-fixing species may alter biogeochemical processes. We hypothesized that the grade of invasion by the N-2-fixer black locust (Robinia pseudoacacia L.) could be related to the distribution and pools of carbon (C) and nitrogen (N) along the profile of two Mediterranean mixed forests of stone pine (Pinus pinea L.) and holm oak (Quercus ilex L.). A low-invaded (LIN) and a high-invaded (HIN) mixed forest were studied. We assessed: N concentration in green and in senescent leaves; C and N pools along the soil profile; seasonal changes of soluble C and N fractions, and microbial activity. Compared to coexisting holm oak and stone pine, black locust had higher N content in green and in senescent leaves. In the mineral soil: N stocks were similar in LIN and HIN; water soluble C and microbial activity, were lower in HIN compared to LIN; water soluble N showed seasonal changes consistent with tree growth activity in both HIN and LIN. In the organic layer of HIN, C and N stocks were about twofold larger than expected on the basis of stand density. Black locust increased C and N stocks in the upper organic layers that are more vulnerable to disturbance. However, it did not increase N stocks in the mineral soil.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: C and N stocks; Exotic N-2-fixing tree; litter; organic layer and mineral soil; Water soluble C and N

Forest microhabitats differentially influence seedling phenology of two co-existing Mediterranean oak species - Monnier, Yogan; Prévosto, Bernard; Ripert, Christian; Corbani, Aude C.; Fernandez, Catherine (Journal of Vegetation Science, 2012)
Question How do forest microhabitats impact seasonal microclimate conditions and phenological seedling strategies in two co-occurring Mediterranean Quercus species with different leaf habits? Location Pinus halepensis woodlands, Provence, SE France. Methods Ninety sets of three acorns of Quercus ilex (evergreen) or Quercus pubescens (winter-deciduous) were sown under various P. halepensis canopy cover conditions. Canopy cover and litter depth were measured at each sowing point, and soil moisture and temperature were measured twice monthly. Seedling phenology and aerial development were monitored during the second growing season under different microhabitats. Results During rainy periods, soil moisture was higher under open canopy and thinner litter layers, whereas during summer drought soil moisture was higher under dense canopy and thicker litter layers. Quercus pubescens seedlings had higher growth activity than Q. ilex before summer drought, whereas the pattern reversed during autumnal growth. Dense canopy cover strongly delayed budburst and decreased foliar development in Q. pubescens, which was more affected than Q. ilex. Depending on species phenology, litter thickness can influence height growth of flushes during early summer. Conclusions Quercus pubescens has a phenological strategy to allow development of maximal foliar area before summer drought, a typical growth strategy of Mediterranean winter-deciduous species. In contrast, later phenological activity of evergreen Q. ilex enables it to cope with the dry period and capitalize on autumnal precipitation events. Dense cover acts as shelter in the dry season but can reduce soil moisture during wetter seasons. In contrast to Q. ilex, Q. pubescens appeared strongly dependent on canopy cover, suggesting that Q. ilex has a larger regeneration niche in Aleppo pine woodlands. In the context of global change, this ‘microhabitat effect’ on species-specific phenological strategy underlines the need to consider effects of local environmental conditions on regenerating species.
Keywords: Canopy; litter; Phenology; Quercus ilex; Quercus pubescens; Soil moisture; Survival

Litter flammability in oak woodlands and shrublands of southeastern France - Curt, Thomas; Schaffhauser, Alice; Borgniet, Laurent; Dumas, Claire; Estève, Roland; Ganteaume, Anne; Jappiot, Marielle; Martin, Willy; N’Diaye, Aminata; Poilvet, Benjamin (Forest Ecology and Management, 2011)
Characterizing the ﬂammability of litter fuels is of major importance for assessing wildland ﬁre ignition hazard. Here we compared the ﬂammability of litter within a mosaic of Quercus suber (cork oak) woodlands and shrublands in a Mediterranean ﬁre-prone area (Maures massif, southeastern France) to test whether the characteristics and the ﬂammability of litter vary with the vegetation types. We tested experimentally the ignitability, the sustainability, the combustibility and the consumability of undisturbed (=non-reconstructed) litter samples with a point-source mode of ignition. Although the frequency of ignition was similar between all the vegetation types, we distinguished four groups having litter of speciﬁc composition and ﬂammability: low and sparse shrublands dominated by Cistus species, medium shrublands with cork oak, high Erica shrublands with sparse cork oak woodlands, and mixed mature oak woodlands with Q. suber, Q. ilex and Q. pubescens. As these vegetation types corresponded to a speciﬁc range of past ﬁre recurrence, we also tested the effect of the number of ﬁres and the time since the last ﬁre on litter ﬂammability. Litters of plots recurrently burned had low ability to propagate ﬂames and low ﬂame sustainability. We discuss how the recent ﬁre history can modify vegetation and litter ﬂammability, and thus the ﬁre ignition hazard.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Fire ignition hazard; flammability; litter; Point-source ignition; Quercus suber; Shrubland

Non-enzymatic hydrolysis of fluorescein diacetate (FDA) in a Mediterranean oak (Quercus ilex L.) litter - Alarcón-Gutiérrez, E; Floch, C; Ruaudel, F; Criquet, S (European Journal of Soil Science, 2008)
We show the presence of interfering substances when the total microbial activity in litter samples is measured with fluorescein diacetate (FDA), and we propose some methodological modifications to avoid such interference. Three distinct litter layers (the OhLn, the OhLv and the OhLf) of evergreen oak (Quercus ilex L.) were characterized by 13C CPMAS NMR and the spectra show that the recalcitrant aromatic and phenolic compounds increase with the degree of degradation of litter. A wide range of sources of interference in the hydrolysis of FDA was found. To understand the origin of this interference, sterilized litter materials (i.e. γ-irradiated or autoclaved) and a wide range of organic substances (i.e. amino acids, glucose, sorbitol and organic humic acids) were investigated. Insignificant differences on the FDA hydrolysis activity (FDA activity) were found in the γ-irradiated and non-irradiated OhLn litter, indicating that γ-irradiation does not destroy enzymes. Conversely, after heat-sterilization of litter, samples showed FDA activity corresponding to 60, 34.8 and 30.8% (in the OhLn, the OhLv and the OhLf layers, respectively) of that of control litters. This indicates the presence of non-enzymatic interfering substances in the FDA assays. As the humification and litter depth increased, hydrolysis of FDA due to interferences decreased, indicating degradation and/or chelation of interfering substances. We hypothesize that lysine, arginine, histidine and cysteine are mainly responsible for the hydrolysis of FDA. We suggest that the use of phosphate buffer (50 mm, pH 7.0) with incubation < 30 minutes, in combination with a temperature between 30 and 40°C, produces insignificant interference in the determination of the final FDA activity in litter samples.
Keywords: CPMAS 13C NMR spectroscopy (voyant); hydrolysis; litter; Soil

Non-enzymatic hydrolysis of fluorescein diacetate (FDA) in a Mediterranean oak (Quercus ilex L.) litter - Alarcón-Gutiérrez, E.; Floch, C.; Ruaudel, F.; Criquet, S. (European Journal of Soil Science, 2008)
We show the presence of interfering substances when the total microbial activity in litter samples is measured with fluorescein diacetate (FDA), and we propose some methodological modifications to avoid such interference. Three distinct litter layers (the OhLn, the OhLv and the OhLf) of evergreen oak (Quercus ilex L.) were characterized by 13C CPMAS NMR and the spectra show that the recalcitrant aromatic and phenolic compounds increase with the degree of degradation of litter. A wide range of sources of interference in the hydrolysis of FDA was found. To understand the origin of this interference, sterilized litter materials (i.e. γ-irradiated or autoclaved) and a wide range of organic substances (i.e. amino acids, glucose, sorbitol and organic humic acids) were investigated. Insignificant differences on the FDA hydrolysis activity (FDA activity) were found in the γ-irradiated and non-irradiated OhLn litter, indicating that γ-irradiation does not destroy enzymes. Conversely, after heat-sterilization of litter, samples showed FDA activity corresponding to 60, 34.8 and 30.8% (in the OhLn, the OhLv and the OhLf layers, respectively) of that of control litters. This indicates the presence of non-enzymatic interfering substances in the FDA assays. As the humification and litter depth increased, hydrolysis of FDA due to interferences decreased, indicating degradation and/or chelation of interfering substances. We hypothesize that lysine, arginine, histidine and cysteine are mainly responsible for the hydrolysis of FDA. We suggest that the use of phosphate buffer (50 mm, pH 7.0) with incubation < 30 minutes, in combination with a temperature between 30 and 40°C, produces insignificant interference in the determination of the final FDA activity in litter samples.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: CPMAS 13C NMR spectroscopy (voyant); hydrolysis; litter; Soil

Endoglucanase and β-glycosidase activities in an evergreen oak litter: annual variation and regulating factors - Criquet, S.; Tagger, S.; Vogt, G.; Le petit, J. (Soil Biology and Biochemistry, 2002)
This paper represents the third part of a larger study about the processes involved in litter biodegradation in an oak copse in France. It concerns the variations in activities of endoglucanases and of β-glycosidases over 13 months in forest litter. Evergreen oak (Quercus ilex L.) litter was taken as a model because Q. ilex is the most abundant tree species in forests of the French Mediterranean area. The activities of several endoglucanases and β-glycosidases, and the concentrations of the proteins and reducing sugars were measured in the evergreen oak litter between October 1997 and October 1998. Several biotic and abiotic factors, potentially involved in the regulation of the activities of these hydrolyzing enzymes, were also measured: culturable heterotrophic bacteria, cellulolytic bacteria and cellulolytic fungi, moisture, temperature and pH of the litter. Under this Mediterranean climate, the moisture of the litter was strongly correlated with many factors and is likely to be important in regulating the temporal dynamics of various biological parameters. A multiple regression analysis showed that the annual dynamic of the culturable heterotrophic bacteria was primarily influenced by moisture but also by variations in concentration of reducing sugars in the litter. Moreover, these bacteria were correlated with the activities of several β-glycosidases, and specifically with the N-acetyl-glucosaminidases (r=0.93). No relationships were established between the number of cellulolytic microorganisms (bacteria and fungi) and the activities of endoglucanases (i.e. cellulases and hemicellulases). The seasonal trends of certain biotic processes, and the influence of pH and of temperature on these processes are also discussed. Electrophoretic analyses were used to estimate the number of cellulase and xylanase isoenzymes in the litter, and to study their fluctuations over one year. The prevailing cellulase isoenzyme had a Rf of 0.64, and there was no relationship between the abundance of cellulolytic microorganisms and the electrophoretic profiles of the cellulases. In the case of the xylanases, the electrophoretic profiles were homogenous throughout the year, and the prevailing xylanase had a Rf of 0.75.
Keywords: Cellulase; hemicellulase; Isoenzymes; litter; Polysaccharides

Endoglucanase and β-glycosidase activities in an evergreen oak litter: annual variation and regulating factors - Criquet, S; Tagger, S; Vogt, G; Le petit, J (Soil Biology and Biochemistry, 2002)
This paper represents the third part of a larger study about the processes involved in litter biodegradation in an oak copse in France. It concerns the variations in activities of endoglucanases and of β-glycosidases over 13 months in forest litter. Evergreen oak (Quercus ilex L.) litter was taken as a model because Q. ilex is the most abundant tree species in forests of the French Mediterranean area. The activities of several endoglucanases and β-glycosidases, and the concentrations of the proteins and reducing sugars were measured in the evergreen oak litter between October 1997 and October 1998. Several biotic and abiotic factors, potentially involved in the regulation of the activities of these hydrolyzing enzymes, were also measured: culturable heterotrophic bacteria, cellulolytic bacteria and cellulolytic fungi, moisture, temperature and pH of the litter. Under this Mediterranean climate, the moisture of the litter was strongly correlated with many factors and is likely to be important in regulating the temporal dynamics of various biological parameters. A multiple regression analysis showed that the annual dynamic of the culturable heterotrophic bacteria was primarily influenced by moisture but also by variations in concentration of reducing sugars in the litter. Moreover, these bacteria were correlated with the activities of several β-glycosidases, and specifically with the N-acetyl-glucosaminidases (r=0.93). No relationships were established between the number of cellulolytic microorganisms (bacteria and fungi) and the activities of endoglucanases (i.e. cellulases and hemicellulases). The seasonal trends of certain biotic processes, and the influence of pH and of temperature on these processes are also discussed. Electrophoretic analyses were used to estimate the number of cellulase and xylanase isoenzymes in the litter, and to study their fluctuations over one year. The prevailing cellulase isoenzyme had a Rf of 0.64, and there was no relationship between the abundance of cellulolytic microorganisms and the electrophoretic profiles of the cellulases. In the case of the xylanases, the electrophoretic profiles were homogenous throughout the year, and the prevailing xylanase had a Rf of 0.75.
Keywords: Cellulase; hemicellulase; Isoenzymes; litter; Polysaccharides

Measurement and characterization of cellulase activity in sclerophyllous forest litter. - Criquet, Stéven (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.
The following values have no corresponding Zotero field: accession-num: 11997167
Keywords: Buffers; Cellulase; Cellulase: analysis; Cellulase: isolation & purification; Cellulose; Cellulose: metabolism; Endoglucanase; Extraction; Hydrogen-Ion Concentration; Isoenzyme; Isoenzymes; Isoenzymes: analysis; litter; Plant Leaves; Plant Leaves: enzymology; Quercus; Quercus: enzymology; Temperature; Trees

Measurement and characterization of cellulase activity in sclerophyllous forest litter. - Criquet, Stéven (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.
Keywords: Buffers; Cellulase; Cellulase: analysis; Cellulase: isolation & purification; Cellulose; Cellulose: metabolism; Endoglucanase; Extraction; Hydrogen-Ion Concentration; Isoenzyme; Isoenzymes; Isoenzymes: analysis; litter; Plant Leaves; Plant Leaves: enzymology; Quercus; Quercus: enzymology; Temperature; Trees

Annual variations of phenoloxidase activities in an evergreen oak litter: influence of certain biotic and abiotic factors - Criquet, S.; Farnet, A. M.; Tagger, S.; Petit, J. Le (Soil Biology and Biochemistry, 2000)
This study concerns ligninolysis phenomena occurring over 13 months in forest litter. Evergreen oak (Quercus ilex L.) litter was taken as a model because Quercus ilex L. is the most abundant tree species in forests of the French Mediterranean area. Several biotic and abiotic factors potentially involved in transformations of polyphenolic compounds, were measured between October 1997 and October 1998. These factors were: global fungal micro¯ora, the fungi producing phenoloxidases (PO+ ), the activities of several phenoloxidases, hydrosoluble phenols, and temperature, humidity and pH of the litter. Results showed that the annual dynamics of fungi and phenoloxidase activities appear to be seasonal, i.e. that these biotic factors such as, were optimal in autumn. A multiple regression analysis showed that there was no correlation between biotic factors such as, fungal populations and phenoloxidase activity and abiotic factors such as, temperature, humidity and pH. Laccases were the preponderant phenoloxidase activities during the year, while those of Mn-peroxidases only appeared in the autumn of 1997. Other phenoloxidases, lignin-peroxidases and tyrosinases were never detected. Interactions between laccases and humic substances were also investigated. Adsorption of laccases on humic substances leads to a shift in the optimal temperature activity of these enzymes from 50 to 308C. Activities of laccases also shifted towards more acidic values when laccases were not adsorbed on humic substances. Nevertheless, the optimal pH was the same (5.7) whether laccases were adsorbed or not to humic substances. Electrophoresis analysis showed little variations in the number of phenoloxidase isoenzymes. Indeed, laccases showed three isoenzymes during the year (Rf 0.23, 0.34 and 0.43). Only one isoform of Mn-peroxidase, with an Rf 0.21, was detected in the litter
Keywords: fungi; humic substances; laccase; litter; peroxidase

Annual variations of phenoloxidase activities in an evergreen oak litter: influence of certain biotic and abiotic factors - Criquet, S; Farnet, A M; Tagger, S; Petit, J Le (Soil Biology and Biochemistry, 2000)
This study concerns ligninolysis phenomena occurring over 13 months in forest litter. Evergreen oak (Quercus ilex L.) litter was taken as a model because Quercus ilex L. is the most abundant tree species in forests of the French Mediterranean area. Several biotic and abiotic factors potentially involved in transformations of polyphenolic compounds, were measured between October 1997 and October 1998. These factors were: global fungal micro¯ora, the fungi producing phenoloxidases (PO+ ), the activities of several phenoloxidases, hydrosoluble phenols, and temperature, humidity and pH of the litter. Results showed that the annual dynamics of fungi and phenoloxidase activities appear to be seasonal, i.e. that these biotic factors such as, were optimal in autumn. A multiple regression analysis showed that there was no correlation between biotic factors such as, fungal populations and phenoloxidase activity and abiotic factors such as, temperature, humidity and pH. Laccases were the preponderant phenoloxidase activities during the year, while those of Mn-peroxidases only appeared in the autumn of 1997. Other phenoloxidases, lignin-peroxidases and tyrosinases were never detected. Interactions between laccases and humic substances were also investigated. Adsorption of laccases on humic substances leads to a shift in the optimal temperature activity of these enzymes from 50 to 308C. Activities of laccases also shifted towards more acidic values when laccases were not adsorbed on humic substances. Nevertheless, the optimal pH was the same (5.7) whether laccases were adsorbed or not to humic substances. Electrophoresis analysis showed little variations in the number of phenoloxidase isoenzymes. Indeed, laccases showed three isoenzymes during the year (Rf 0.23, 0.34 and 0.43). Only one isoform of Mn-peroxidase, with an Rf 0.21, was detected in the litter
Keywords: fungi; humic substances; laccase; litter; peroxidase

Biochemical and molecular characterization of a laccase from Marasmius quercophilus - Dedeyan, B; Klonowska, A; Tagger, S; Tron, T; Iacazio, G; Gil, G; Le petit, J (APPLIED AND ENVIRONMENTAL MICROBIOLOGY, 2000)
The basidiomycete Marasmius quercophilus is commonly found during autumn on the decaying litter of the evergreen oak (Quercus ilex L.), a plant characteristic of Mediterranean forest. This white-rot fungus colonizes the leaf surface with rhizomorphs, causing a total bleaching of the leaf. In synthetic liquid media, this white-rot fungus has strong laccase activity. From a three-step chromatographic procedure, we purified a major isoform to homogeneity, The gene encodes a monomeric glycoprotein of approximately 63 kDa, with a 3.6 isoelectric point, that contains 12% carbohydrate, Spectroscopic analysis of the purified enzyme (UV/visible and electron paramagnetic resonance, atomic absorption) confirmed that it belongs to the ``blue copper oxidase{''} family. With syringaldazine as the substrate, the enzyme's pH optimum was 4.5, the optimal temperature was 75 degrees C, and the K-m was 7.1 mu M. The structural gene, lac1, was cloned and sequenced. This gene encodes a 517-amino-acid protein 99% identical to a laccase produced by PM1, an unidentified basidiomycete previously isolated from wastewater from a paper factory in Spain. This similarity may be explained by the ecological distribution of the evergreen oak in Mediterranean forest.
Keys: APS
Keywords: Basidiomycete; litter; Marasmius quercophilus; mediterranean forest; Quercus ilex L.; structural genes

Biochemical and molecular characterization of a laccase from Marasmius quercophilus - Dedeyan, B.; Klonowska, A.; Tagger, S.; Tron, T.; Iacazio, G.; Gil, G.; Le petit, J. (APPLIED AND ENVIRONMENTAL MICROBIOLOGY, 2000)
The basidiomycete Marasmius quercophilus is commonly found during autumn on the decaying litter of the evergreen oak (Quercus ilex L.), a plant characteristic of Mediterranean forest. This white-rot fungus colonizes the leaf surface with rhizomorphs, causing a total bleaching of the leaf. In synthetic liquid media, this white-rot fungus has strong laccase activity. From a three-step chromatographic procedure, we purified a major isoform to homogeneity, The gene encodes a monomeric glycoprotein of approximately 63 kDa, with a 3.6 isoelectric point, that contains 12% carbohydrate, Spectroscopic analysis of the purified enzyme (UV/visible and electron paramagnetic resonance, atomic absorption) confirmed that it belongs to the ``blue copper oxidase{''} family. With syringaldazine as the substrate, the enzyme's pH optimum was 4.5, the optimal temperature was 75 degrees C, and the K-m was 7.1 mu M. The structural gene, lac1, was cloned and sequenced. This gene encodes a 517-amino-acid protein 99% identical to a laccase produced by PM1, an unidentified basidiomycete previously isolated from wastewater from a paper factory in Spain. This similarity may be explained by the ecological distribution of the evergreen oak in Mediterranean forest.
Keys: APSKeys: APSThe following values have no corresponding Zotero field: pub-location: 1325 MASSACHUSETTS AVENUE, NW, WASHINGTON, DC 20005-4171 USA publisher: AMER SOC MICROBIOLOGY
Keywords: Basidiomycete; litter; Marasmius quercophilus; mediterranean forest; Quercus ilex L.; structural genes

Laccase activity of forest litter - Criquet, S; Tagger, S; Vogt, G (Soil Biology and Biochemistry, 1999)
Laccases are blue-copper enzymatic proteins involved in the transformation of polyphenolic compounds, such as lignin, into forest litter. A method to measure their activity was developed using an evergreen oak litter as a model system. We considered factors that aect the extraction of these enzymes and the measurement of their activity. The factors studied included powdering of the leaves, adding polyvinylpolypyrrolidone or Tween 80, adsorption of enzymes on centrifugation pellets, concentration of the extracts, nature and molarity of the extraction solvent, amount of powdered leaves used for enzymatic extraction, extraction time, pH, and temperature during the measurement of the activity
Keywords: Extraction; laccase; litter

Laccase activity of forest litter - Criquet, S.; Tagger, S.; Vogt, G. (Soil Biology and Biochemistry, 1999)
Laccases are blue-copper enzymatic proteins involved in the transformation of polyphenolic compounds, such as lignin, into forest litter. A method to measure their activity was developed using an evergreen oak litter as a model system. We considered factors that aect the extraction of these enzymes and the measurement of their activity. The factors studied included powdering of the leaves, adding polyvinylpolypyrrolidone or Tween 80, adsorption of enzymes on centrifugation pellets, concentration of the extracts, nature and molarity of the extraction solvent, amount of powdered leaves used for enzymatic extraction, extraction time, pH, and temperature during the measurement of the activity
Keywords: Extraction; laccase; litter

Field decomposition of leaf litters: earthworm–microorganism interactions—the ploughing-in effect - Cortez, J; Bouché, M B (Soil Biology and Biochemistry, 1998)
We describe a new decomposition model including the consequences of earthworm mechan- ical activity, especially the ploughing-in eect. In an experiment we tested this ploughing-in eect on the disappearance of leaf litter from four tree species (sessile oak, Quercus petraea L., holm oak, Quer- cus ilex L., sweet chestnut, Castanea sativa Mill and beech, Fagus sylvatica L.) during two 2 y exposure at the site of Anduze which contained the highest earthworm biomass. Our experiment, carried out with leaf litter placed in litterbags allowing (0.5 cm mesh size) or preventing (0.1 cm mesh size) the access of earthworms, con®rms (1) the rates of litter decomposition observed in the ®rst experiment and (2) the important eect of earthworms on litter decomposition (from 20.5% to 30.2% depending on the litter). The breakdown of the dierent litters by soil fauna varied from 24.2% to 40.6% depending on the litters after 2 y exposure in the ®eld at Anduze and the litter decomposition rate was increased by a mean factor of about 5.2. We describe a technique for detecting litter contamination attributed to earthworm casts. This technique is based on the change of the litter total weight loss (TWL)-to-litter total C loss (TCL) ratios which varied from 0.652 to 0.915 in the presence of earthworms and were close to 1 (from 0.952 to 0.995) in the absence of earthworms. We assumed that this large change in these ratios indicated a mineral contamination of litters due to earthworm casting. This hypothesis was con®rmed by the litter ash contents varying from 2.6% to 9.6% with earthworms and from 1.3% to 2.1% without earthworms only. These results point out the ecological importance of contamination of the litter by casts during decomposition.
Keywords: decomposition; earthworm; litter; microbial decomposition; ploughing-in (voyant); weight loss

Field decomposition of leaf litters: earthworm–microorganism interactions—the ploughing-in effect - Cortez, J.; Bouché, M. B. (Soil Biology and Biochemistry, 1998)
We describe a new decomposition model including the consequences of earthworm mechan- ical activity, especially the ploughing-in eect. In an experiment we tested this ploughing-in eect on the disappearance of leaf litter from four tree species (sessile oak, Quercus petraea L., holm oak, Quer- cus ilex L., sweet chestnut, Castanea sativa Mill and beech, Fagus sylvatica L.) during two 2 y exposure at the site of Anduze which contained the highest earthworm biomass. Our experiment, carried out with leaf litter placed in litterbags allowing (0.5 cm mesh size) or preventing (0.1 cm mesh size) the access of earthworms, con®rms (1) the rates of litter decomposition observed in the ®rst experiment and (2) the important eect of earthworms on litter decomposition (from 20.5% to 30.2% depending on the litter). The breakdown of the dierent litters by soil fauna varied from 24.2% to 40.6% depending on the litters after 2 y exposure in the ®eld at Anduze and the litter decomposition rate was increased by a mean factor of about 5.2. We describe a technique for detecting litter contamination attributed to earthworm casts. This technique is based on the change of the litter total weight loss (TWL)-to-litter total C loss (TCL) ratios which varied from 0.652 to 0.915 in the presence of earthworms and were close to 1 (from 0.952 to 0.995) in the absence of earthworms. We assumed that this large change in these ratios indicated a mineral contamination of litters due to earthworm casting. This hypothesis was con®rmed by the litter ash contents varying from 2.6% to 9.6% with earthworms and from 1.3% to 2.1% without earthworms only. These results point out the ecological importance of contamination of the litter by casts during decomposition.
Keywords: decomposition; earthworm; litter; microbial decomposition; ploughing-in (voyant); weight loss

MIGRATION STUDY OF RADIONUCLIDES IN A MEDITERRANEAN FOREST SOIL USING SYNTHETIC AEROSOLS - SAURAS, T; ROCA, M C; Tent, J; Llauradó, M; VIDAL, M; Rauret, G; Vallejo, V R (SCIENCE OF THE TOTAL ENVIRONMENT, 1994)
Radionuclide migration in a Mediterranean forest was studied in field conditions. Fresh Holm oak leaves were exposed to a synthetic aerosol including Cs-134, Sr-85 and Ag-110m, and were incubated in the original Holm oak forest in two types of cylinder: (1) cylinders in which the contaminated litter lies directly on the original F layer; (2) cylinders with an exchange resin bag inserted between the contaminated litter and the underlying F layer. The results for 232 days of incubation showed that Cs-134 presented an initial rapid leaching period, which corresponded to the fraction extracted with water from the initially contaminated leaves. Further Cs-134 release was related to litter decompostiion. Sr-85 migration was studied for only 76 days, and its behaviour appeared to be similar to Cs-134. Both radionuclides migrated within the litter leachates. After 3 months of incubation, around 70% of the initial Cs-134 was transferred to the underlying layers, mainly to the F layer. Cs-134 absorbed into the leaves was released at the same rates as K. The Ag-110m activity lost from the contaminated litter amounted to around 45% in the open cylinders, from which 15-20% was attributed to the effect of soil faunal activity. The field method proposed proved to be useful in describing radionuclide migration in situ and the mechanisms involved.
Keywords: litter; mediterranean forest; RADIONUCLIDE MIGRATION

SUCCESSION OF BACTERIA ATTACHED TO EVERGREEN OAK LEAF SURFACES - Périssol, C; Roux, M; LEPETIT, J (EUROPEAN JOURNAL OF SOIL BIOLOGY, 1993)
Heterotrophic attached bacteria were isolated from evergreen oak leaf surfaces (Quercus ilex L.) on both phylloplane and litter at each season during one year. Few epiphytic bacteria were recovered from the phylloplane (18 %) in comparison with the litter. The data derived from the 324 strains were subjected to cluster analysis. The taxonomic structure displayed 44 phenetic groups. The bacterial communities on leaf surfaces belonged mainly to two genera: Bacillus (31 %), present on both phylloplane and litter, and Pseudomonas (35 %) present only on the litter. Some communities of Bacillus were able to degrade structural chemical components of the leaf, such as pectins or lignin monomers. The Bacillus isolates were generally more numerous in spring and in summer, i.e. during the warm seasons, whereas Pseudomonas predominated in autumn and winter. In vitro measurements of strains growth rates showed moreover that Bacillus strains grew better at 40-degrees-C than Pseudomonas strains. A climate-related factor, namely temperature, has therefore a great influence on the natural selection process of these communities. Another seasonal succession was observed, involving two genera: Xanthomonas predominant in winter and Lactobacillus in summer, as well as the Enterobacteriaceae family in autumn.
Keywords: ATTACHED BACTERIA; leaves; litter; PHYLLOPLANE

QUERCUS-ILEX L LITTER DECOMPOSITION AND MINERAL EVOLUTION IN AN EVERGREEN OAK WOODLAND IN MAJORCA (BALEARIC-ISLANDS, SPAIN) - XAMENA, J; García, C; MOREY, M (RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES, 1992)
The aim of this contribution is to describe the decomposition processes of litter in an evergreen oak wood and the evolution of the four cations; calcium, magnesium, sodium and potassium.
Keywords: decomposition; litter; minerals